Building a learning environment in mental healthcare education through warm-up exercises - Ingrid Femdal (Scandinavian University Press (Universitetsforlaget), 2021)
Background: Students in mental health care education can learn from experiences in clinical situations by using drama. Warm-up exercises can provide students with activities which generate engagement and enthusiasm for the learning experiences that follow, and create a safe learning environment where students can feel comfortable to participate. Purpose: To explore and describe mental healthcare students’ experiences of participating in warm-up exercises in a drama workshop. Design: This qualitative study is based on the researchers’ participation in field studies of a drama workshop, and focus group interviews with the students. Findings: The findings indicated that the warm-up exercises provided positive learning experiences, and these are represented in two main categories with related sub-categories: 1) Creating a positive learning environment, and 2) Being involved and engaged in the experience. Originality/Value: This study shows that to achieve safe and engaging learning, the use of warm-up activities can be particularly valuable in encouraging participants to experiment freely and spontaneously with different roles from their clinical experiences.